Identification of COVID-19 infection areas through spatial analysis of urban facilities from Puno, Perú. - Marin Mamani, Grover (2022)
The health crisis of 2020 due to COVID 19 has become the main problem faced by governments, in this context spatial analysis is a tool that would help control the pandemic. The purpose is to identify the COVID 19 contagion risk zones, through the spatial analysis of banking and commercial equipment in the city of Puno. The banking and commercial equipment has been located in UTM WGS 84 coordinates, for the generation of response surfaces using Kernel density, adding the partial results through map algebra and also identified the spatial autocorrelation by means of the Moran I index. The high contagion risk zone COVID 19 has an area of 127 210,44 m2, representing 14% that covers 13 blocks, generating a concentric pattern in the center from Puno city, due to the proximity of banking and commercial equipment, causing inequality with other sectors of the city.